1986
DOI: 10.1128/aem.52.5.1055-1059.1986
|View full text |Cite
|
Sign up to set email alerts
|

Direct fermentation of potato starch to ethanol by cocultures of Aspergillus niger and Saccharomyces cerevisiae

Abstract: Direct fermentation of unhydrolyzed potato starch to ethanol by monocultures of an amylolytic fungus, Aspergilus niger, and cocultures ofA. niger and Saccharomyces cerevisiae was investigated. Amylolytic activity, rate and amount of starch utilization, and ethanol yields increased several-fold in coculture versus the monoculture due to the synergistic metabolic interactions between the species. Optimal ethanol yields were obtained in the pH range 5 to 6 and amylolytic activity was obtained in the pH range 5 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 6 publications
5
35
0
Order By: Relevance
“…Commonly, SSF is conducted by fungi over starch‐rich substrates. Ethanol production , traditional food , citric acid production , and koji fermentation are instances of fungi‐based fermentation processes of starchy matrices. Commonly used fungi strains for SSF include Aspergillus oryzae traditionally used for koji production, and Penicillium roquefortii for cheese production .…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, SSF is conducted by fungi over starch‐rich substrates. Ethanol production , traditional food , citric acid production , and koji fermentation are instances of fungi‐based fermentation processes of starchy matrices. Commonly used fungi strains for SSF include Aspergillus oryzae traditionally used for koji production, and Penicillium roquefortii for cheese production .…”
Section: Introductionmentioning
confidence: 99%
“…In such a process, two organisms with synergistic relationships are co-cultured together in the same vessel. A study has shown that co-culturing of an efficient sugar fermenter such as Saccharomyces cerevisiae with an Aspergillus species in a starch medium would prevent accumulation of inhibitory concentrations of reducing sugar and hence, an enhancement of the amylolytic activity, the amount of starch metabolizable, and the total ethanol yield (Abouzied & Reddy, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Y=normalβ0+normalΣi=1kβiXi+normalΣi=1kβnormalinormaliXi2+Σi=1kΣj=1knormalβijXiXj where, Y represents the response variable, β 0 , β i , β ii , β ij are intercept, linear, quadratic, and interaction constant coefficients, respectively, and k is the numbers of involved variables. The residual starch was also determined for each trials employing phenol–sulphuric acid method .…”
Section: Methodsmentioning
confidence: 99%